Representation of Women to Gender Construction: Analysis of Memoar Comparative Literature of A Women's Doctor and My Hiroko - Hendra Kaprisma (Universitas Negeri Surabaya, 2018)
The marginalization of women's sexuality and its formation as a myth shows that social construction is basically a sexual construction that is primarily directed at defining and mastering womens sexuality. In this article the author discusses how sexual issues on womens stereotypes as displayed in the comparison between the female doctor character in the novel Memoar Seorang Dokter Perempuan by Nawal El Saadawi and Hiroko in the novel Namaku Hiroko by Nh. Dini. The scope of the discussion is limited to the depiction of the two main characters using comparative literary methods. Through the stereotypical analysis of women displayed from both works, it can be seen the link between the ideas of the feminist movement to deconstruct patriarchal culture in the matter of sexuality with the depiction of the two figures. In the end, the stereotype reflected in the two novels have a value of resistance to patriarchal culture. Keywords: deconstruction, comparative literature, sexuality, stereotypes